Modified graphene as well as preparation method and application thereof
By using dispersants and organic acids to modify during the graphene preparation process and mixing them with inorganic corrosion inhibitors and surfactants, the problems of easy agglomeration and poor anti-corrosion coating of traditional graphene are solved, and modified graphene with good corrosion resistance and dispersion properties are prepared.
Patent Information
- Application Number
- CN202411897741.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The effects of traditional graphene-loaded corrosion inhibitors are limited and prone to agglomeration, resulting in a uniform distribution of anticorrosion coatings and reduced protective effects, which may cause cracks and holes.
By mixing the dispersant, organic acid and graphite in the first dispersion medium and performing liquid peeling treatment, a graphene suspension was obtained, and mixed with an inorganic corrosion inhibitor and a surfactant in the second dispersion medium, and undergoing insulation treatment to prepare modified graphene.
The prepared modified graphene has good corrosion resistance and dispersion properties, avoids agglomeration, can be used as a corrosion-proof filler with stable performance, and enhances the density and protection ability of the anticorrosion coating.
Smart Images

Figure CN119613999A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of graphene technology, and in particular to a modified graphene and a preparation method and application thereof. Background Art
[0002] Graphene has good anti-permeability and can be used as an anti-corrosion filler in anti-corrosion coatings to enhance the physical barrier effect of the anti-corrosion coating matrix. At the same time, graphene has an ultra-high specific surface area and can load corrosion inhibitors to further increase the anti-corrosion ability of the anti-corrosion coating.
[0003] However, the effect of traditional graphene-loaded corrosion inhibitors is limited, and due to the strong π-π interaction and van der Waals force between graphene layers, graphene is prone to agglomeration. This will not only hinder the uniform distribution of graphene in the anti-corrosion coating and reduce the protective effect, but may also cause cracks and voids in the anti-corrosion coating, resulting in a decrease in the density and protective ability of the anti-corrosion coating. Summary of the invention
[0004] Based on this, it is necessary to provide a modified graphene and its preparation method and application. The preparation method of the modified graphene of the present application can prepare modified graphene with good anti-corrosion performance, good dispersion performance and not easy to agglomerate, so that it can be used as an anti-corrosion filler with stable performance.
[0005] In a first aspect, the present application provides a method for preparing modified graphene, comprising the following steps:
[0006] Mixing a dispersant, an organic acid and graphite in a first dispersion medium to obtain a first dispersion system, and performing a liquid phase exfoliation treatment on the first dispersion system to obtain a graphene suspension;
[0007] Removing unpeeled graphite from the graphene suspension to obtain a graphene dispersion;
[0008] Performing solid-liquid separation on the graphene dispersion to obtain a solid-phase graphene raw material;
[0009] The solid-phase graphene raw material, the inorganic corrosion inhibitor and the surfactant are mixed in a second dispersion medium to obtain a second dispersion system, and the second dispersion system is subjected to a heat preservation treatment.
[0010] In some embodiments, the dispersant includes at least one of polyvinyl alcohol, dopamine, sodium polystyrene sulfonate, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone.
[0011] In some embodiments, the organic acid includes at least one of citric acid, phytic acid, acetic acid and ascorbic acid.
[0012] In some embodiments, the inorganic corrosion inhibitor includes at least one of cerium nitrate, cerium chloride, lanthanum nitrate, lanthanum chloride, lanthanum carbonate, sodium silicate, sodium phosphate and sodium molybdate.
[0013] In some embodiments, the graphite is 300-1000 mesh graphite.
[0014] In some embodiments, in the first dispersed system, the mass ratio of the organic acid to the graphite is (1-2):10.
[0015] In some embodiments, in the first dispersed system, the mass ratio of the dispersant to the graphite is (1-2):1.
[0016] In some embodiments, in the first dispersed system, the concentration of the organic acid is 10 mg / mL to 20 mg / mL.
[0017] In some embodiments, in the first dispersed system, the concentration of the dispersant is 1 mg / mL to 2 mg / mL.
[0018] In some embodiments, in the first dispersed system, the concentration of the graphite is 10 mg / mL to 20 mg / mL.
[0019] In some embodiments, in the second dispersed system, the concentration of the solid-phase graphene raw material is 0.5 mg / mL to 2 mg / mL.
[0020] In some embodiments, in the second dispersed system, the concentration of the inorganic corrosion inhibitor is 3 mg / mL to 6 mg / mL.
[0021] In some embodiments, the surfactant includes at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyldimethylbenzylammonium chloride and dodecyldimethylbenzylammonium chloride.
[0022] In some embodiments, in the second dispersed system, the concentration of the surfactant is 2 mg / mL to 10 mg / mL.
[0023] In some embodiments, the temperature of the heat preservation treatment is 40°C to 90°C.
[0024] In some embodiments, the heat preservation treatment time is 2h~3h.
[0025] In some embodiments, a dispersant, an organic acid and graphite are mixed in a first dispersion medium to obtain a first dispersion system, and liquid phase exfoliation treatment of the first dispersion system comprises the following steps:
[0026] Dissolving the dispersant and the organic acid in deionized water to obtain a first solution;
[0027] Dispersing the graphite in a first organic solvent to obtain a first dispersion;
[0028] The first solution and the first dispersion are mixed, and the mixed solution is sheared at a rotation speed of 10000 rpm to 15000 rpm.
[0029] In some embodiments, removing the unexfoliated graphite in the graphene suspension comprises the following steps:
[0030] The graphene suspension is centrifuged at a rotation speed of 500 rpm to 1000 rpm to precipitate the unexfoliated graphite to obtain the graphene dispersion.
[0031] In some embodiments, the solid-liquid separation process of the graphene dispersion comprises the following steps:
[0032] The graphene dispersion is centrifuged at a speed of 9000 rpm to 12000 rpm to obtain a graphene precipitate.
[0033] In some embodiments, after the second dispersed system is subjected to heat preservation treatment, the following steps are further included:
[0034] Centrifuging the second dispersed system at a speed of 9000 rpm to 12000 rpm to obtain a modified graphene precipitate;
[0035] The modified graphene is precipitated and freeze-dried at -40°C to -20°C for 24h to 36h, and then crushed and sieved to obtain modified graphene powder.
[0036] In a second aspect, the present application provides a modified graphene prepared by any of the above-mentioned methods for preparing modified graphene, comprising a graphene body, an organic acid and an inorganic corrosion inhibitor; the inorganic corrosion inhibitor is loaded on the graphene body through the organic acid.
[0037] In a third aspect, the present application provides the use of the modified graphene mentioned above or the modified graphene prepared by the preparation method of modified graphene described in any of the above items as an anti-corrosion filler in an anti-corrosion coating.
[0038] In the preparation method of the above-mentioned modified graphene, by carrying out liquid phase stripping treatment to graphite in the first dispersion medium, it is possible to obtain graphene with a relatively intact lattice structure, so that the key properties such as the permeability resistance of the prepared graphene are not damaged. In the process of liquid phase stripping, graphene is modified by dispersant and organic acid, so that graphene can have good dispersibility, and more active points can also be given to graphene, which helps to promote the interaction between graphene and inorganic corrosion inhibitors, and improves the loading rate of graphene to corrosion inhibitors. At the same time, under the conditions of heat preservation and addition of surfactants, the loading effect of graphene on inorganic corrosion inhibitors is achieved. The preparation method of the modified graphene of the present application can prepare modified graphene with good corrosion resistance, and good dispersion performance, which is not easy to agglomerate, so that it can be used as a stable anti-corrosion filler. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 A schematic flow chart of a method for preparing modified graphene provided in one embodiment of the present application;
[0040] Figure 2 a is the FTIR spectrum of polyvinyl alcohol, graphite and graphene in Example 1 of the present application, Figure 2 b is the Raman spectrum of graphite and graphene in Example 1;
[0041] Figure 3 a is the FTIR spectra of modified graphene, graphene and graphite in Example 1 of the present application, Figure 3 b is the Raman spectra of modified graphene, graphene and graphite in Example 1. DETAILED DESCRIPTION
[0042] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0044] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0045] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0046] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0047] An embodiment of the present application provides a method for preparing modified graphene, comprising the following steps:
[0048] Mixing a dispersant, an organic acid and graphite in a first dispersion medium to obtain a first dispersion system, and performing a liquid phase exfoliation treatment on the first dispersion system to obtain a graphene suspension;
[0049] Removing unpeeled graphite from the graphene suspension to obtain a graphene dispersion;
[0050] Performing solid-liquid separation on the graphene dispersion to obtain a solid-phase graphene raw material;
[0051] The solid-phase graphene raw material, the inorganic corrosion inhibitor and the surfactant are mixed in a second dispersion medium to obtain a second dispersion system, and the second dispersion system is subjected to a heat preservation treatment.
[0052] In the preparation method of the above-mentioned modified graphene, by carrying out liquid phase stripping treatment to graphite in the first dispersion medium, it is possible to obtain graphene with a relatively intact lattice structure, so that the key properties such as the permeability resistance of the prepared graphene are not damaged. In the process of liquid phase stripping, graphene is modified by dispersant and organic acid, so that graphene can have good dispersibility, and more active points can also be given to graphene, which helps to promote the interaction between graphene and inorganic corrosion inhibitors, and improves the loading rate of graphene to corrosion inhibitors. At the same time, under the conditions of heat preservation and addition of surfactants, the loading effect of graphene on inorganic corrosion inhibitors is achieved. The preparation method of the modified graphene of the present application can prepare modified graphene with good corrosion resistance, and good dispersion performance, which is not easy to agglomerate, so that it can be used as a stable anti-corrosion filler.
[0053] Furthermore, organic acids can not only increase the loading rate of inorganic corrosion inhibitors on graphene, but also act as organic ligands to form complexes with metal ions in inorganic corrosion inhibitors, thereby preventing metal ions from hydrolyzing or undergoing other side reactions in the solution, thereby playing a stabilizing connecting role.
[0054] Furthermore, when the modified graphene is used in the anti-corrosion coating on the surface of the metal substrate, the organic acid and the inorganic corrosion inhibitor can synergistically form a protective film on the surface of the metal substrate, playing a synergistic film-forming role. For example, the carboxyl group of citric acid can form a coordination bond with the metal ion, and the cerium ion of cerium nitrate can also react with the active site on the metal surface. The protective film formed by the combined action of the two can better prevent the contact of corrosive media such as oxygen and water with the metal substrate, thereby enhancing the anti-corrosion effect.
[0055] Reference Figure 1 As shown, in some embodiments, the method for preparing modified graphene comprises the following steps:
[0056] S10: mixing a dispersant, an organic acid and graphite in a first dispersion medium to obtain a first dispersion system, and performing a liquid phase exfoliation treatment on the first dispersion system to obtain a graphene suspension.
[0057] In some embodiments, the dispersant includes at least one of polyvinyl alcohol, dopamine, sodium polystyrene sulfonate, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone.
[0058] In some embodiments, the organic acid includes at least one of citric acid, phytic acid, acetic acid, and ascorbic acid.
[0059] In some embodiments, the graphite is 300-1000 mesh graphite.
[0060] Optionally, the graphite is 300 mesh, 400 mesh, 500 mesh, 600 mesh, 700 mesh, 800 mesh, 900 mesh or 1000 mesh, or the graphite may be graphite within a range between any two of the above mesh sizes.
[0061] In some embodiments, the graphite is flake graphite.
[0062] In some of the embodiments, in the first dispersed system, the mass ratio of the organic acid to the graphite is (1-2):10.
[0063] In the first dispersed system, when the mass ratio of the organic acid to the graphite is too low, the long-term dispersion performance of the prepared modified graphene is poor, and when the mass ratio of the organic acid to the graphite is too high, it will cause a waste of raw materials. Optionally, in the first dispersed system, the mass ratio of the organic acid to the graphite is 1:10, 1.1:10, 1.2:10, 1.3:10, 1.4:10, 1.5:10, 1.6:10, 1.7:10, 1.8:10, 1.9:10 or 2:10, or, in the first dispersed system, the mass ratio of the organic acid to the graphite can also be within the range between any two of the above mass ratios.
[0064] In some of the embodiments, in the first dispersed system, the mass ratio of the dispersant to the graphite is (1-2):1.
[0065] In the first dispersed system, when the mass ratio of the dispersant to the graphite is too low, the long-term dispersion performance of the prepared modified graphene is poor, and when the mass ratio of the dispersant to the graphite is too high, it will cause waste of raw materials. Optionally, in the first dispersed system, the mass ratio of the dispersant to the graphite is 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, or, in the first dispersed system, the mass ratio of the dispersant to the graphite can also be within the range between any two of the above mass ratios.
[0066] In some embodiments, in the first dispersed system, the concentration of the organic acid is 10 mg / mL to 20 mg / mL.
[0067] Optionally, in the first dispersed system, the concentration of the organic acid is 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL or 20 mg / mL, or, in the first dispersed system, the concentration of the organic acid may also be within the range between any two of the above concentrations.
[0068] In some embodiments, in the first dispersed system, the concentration of the dispersant is 1 mg / mL to 2 mg / mL.
[0069] Optionally, in the first dispersed system, the concentration of the dispersant is 1 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL, 1.5 mg / mL, 1.6 mg / mL, 1.7 mg / mL, 1.8 mg / mL, 1.9 mg / mL or 2 mg / mL, or, in the first dispersed system, the concentration of the dispersant may also be within the range between any two of the above concentrations.
[0070] In some embodiments, in the first dispersed system, the concentration of graphite is 10 mg / mL to 20 mg / mL.
[0071] Optionally, in the first dispersed system, the concentration of graphite is 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL or 20 mg / mL, or, in the first dispersed system, the concentration of graphite may also be within the range between any two of the above concentrations.
[0072] In some embodiments, a dispersant, an organic acid and graphite are mixed in a first dispersion medium to obtain a first dispersion system, and liquid phase exfoliation treatment of the first dispersion system comprises the following steps:
[0073] dissolving a dispersant and an organic acid in deionized water to obtain a first solution;
[0074] dispersing graphite in a first organic solvent to obtain a first dispersion;
[0075] The first solution and the first dispersion are mixed, and the mixed solution is sheared at a rotation speed of 10000 rpm to 15000 rpm.
[0076] Through the above-mentioned liquid phase exfoliation treatment, a better exfoliation effect of graphite can be achieved to obtain graphene with a layered structure.
[0077] In some embodiments, the shearing treatment time is 1 h to 2 h.
[0078] Optionally, the rotation speed of the shearing treatment is 10000 rpm, 11000 rpm, 12000 rpm, 13000 rpm, 14000 rpm or 15000 rpm, or, the rotation speed of the shearing treatment may also be within the range between any two of the above rotation speeds.
[0079] Optionally, the shearing treatment time is 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h, or, the shearing treatment time may also be within the range between any two of the above times.
[0080] In some embodiments, the first organic solvent includes at least one of ethanol, methanol, acetone, ethylene glycol, isopropanol and nitrogen methyl pyrrolidone.
[0081] In some embodiments, the volume ratio of deionized water to the first organic solvent in the first dispersion is 1:(1-1.5).
[0082] Optionally, the volume ratio of deionized water to the first organic solvent in the first dispersion is 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5, or the volume ratio of deionized water to the first organic solvent in the first dispersion may also be within the range between any two of the above volume ratios.
[0083] In some embodiments, dissolving the dispersant and the organic acid in deionized water comprises the following steps:
[0084] Heat the dispersant and organic acid in deionized water to boiling and continue stirring at 70°C to 95°C for 30min to 120min to dissolve the dispersant and organic acid.
[0085] S20: removing unpeeled graphite from the graphene suspension to obtain a graphene dispersion.
[0086] In some embodiments, removing unexfoliated graphite from the graphene suspension comprises the following steps:
[0087] The graphene suspension is centrifuged at a speed of 500 rpm to 1000 rpm to precipitate the unexfoliated graphite to obtain a graphene dispersion.
[0088] Within the above centrifugal speed range, the unexfoliated graphite can be precipitated and the exfoliated graphene with good dispersion effect can be separated. It can be understood that after the above centrifugation of the graphene suspension, the supernatant obtained is the graphene dispersion.
[0089] In some embodiments, the graphene suspension is centrifuged at a speed of 500 rpm to 1000 rpm for 30 min to 60 min.
[0090] Optionally, the speed at which the graphene suspension is centrifuged is 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm, or, the speed at which the graphene suspension is centrifuged may also be within a range between any two of the above speeds.
[0091] Optionally, the time for centrifuging the graphene suspension at a speed of 500 rpm to 1000 rpm is 30 min, 40 min, 50 min or 60 min, or the time for centrifuging the graphene suspension at a speed of 500 rpm to 1000 rpm may also be within the range between any two of the above times.
[0092] S30: performing solid-liquid separation on the graphene dispersion to obtain a solid-phase graphene raw material.
[0093] In some embodiments, the solid-liquid separation process of the graphene dispersion comprises the following steps:
[0094] The graphene dispersion is centrifuged at a speed of 9000 rpm to 12000 rpm to obtain graphene precipitation.
[0095] In the above-mentioned centrifugal rotation speed range, the graphene in the graphene dispersion can be precipitated to achieve solid-liquid separation and obtain a solid-phase graphene raw material.
[0096] In some embodiments, the graphene dispersion is centrifuged at a speed of 9000 rpm to 12000 rpm for 30 min to 60 min.
[0097] Optionally, the rotation speed of centrifuging the graphene dispersion is 9000 rpm, 10000 rpm, 11000 rpm or 12000 rpm, or the rotation speed of centrifuging the graphene dispersion may also be within the range between any two of the above rotation speeds.
[0098] Optionally, the time for centrifuging the graphene dispersion at a speed of 9000 rpm to 12000 rpm is 30 min, 40 min, 50 min or 60 min, or the time for centrifuging the graphene dispersion at a speed of 9000 rpm to 12000 rpm may also be within the range between any two of the above times.
[0099] S40: mixing the solid-phase graphene raw material, the inorganic corrosion inhibitor and the surfactant in a second dispersion medium to obtain a second dispersion system, and performing heat preservation treatment on the second dispersion system.
[0100] In some embodiments, the inorganic corrosion inhibitor includes at least one of cerium nitrate, cerium chloride, lanthanum nitrate, lanthanum chloride, lanthanum carbonate, sodium silicate, sodium phosphate and sodium molybdate.
[0101] In some embodiments, in the second dispersed system, the concentration of the inorganic corrosion inhibitor is 3 mg / mL to 6 mg / mL.
[0102] Optionally, in the second dispersed system, the concentration of the inorganic corrosion inhibitor is 3 mg / mL, 3.5 mg / mL, 4 mg / mL, 4.5 mg / mL, 5 mg / mL, 5.5 mg / mL or 6 mg / mL, or, in the second dispersed system, the concentration of the inorganic corrosion inhibitor may also be within the range between any two of the above concentrations.
[0103] In some of the embodiments, in the second dispersed system, the concentration of the solid-phase graphene raw material is 0.5 mg / mL to 2 mg / mL.
[0104] Optionally, in the second dispersed system, the concentration of the solid-phase graphene raw material is 0.5 mg / mL, 0.75 mg / mL, 1 mg / mL, 1.25 mg / mL, 1.5 mg / mL, 1.75 mg / mL or 2 mg / mL, or, in the second dispersed system, the concentration of the solid-phase graphene raw material may also be within the range between any two of the above concentrations.
[0105] In the second dispersed system, within the concentration range of the above-mentioned inorganic corrosion inhibitor and solid-phase graphene raw material, a better loading effect of graphene on the inorganic corrosion inhibitor can be achieved.
[0106] In some embodiments, the temperature of the heat preservation treatment is 40°C to 90°C.
[0107] Optionally, the temperature of the heat preservation treatment is 40°C, 50°C, 60°C, 70°C, 80°C or 90°C, or, the temperature of the heat preservation treatment may also be within the range between any two of the above temperatures.
[0108] In some embodiments, the heat preservation time is 2h~3h.
[0109] Optionally, the heat preservation treatment time is 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, or, the heat preservation treatment time may also be within the range between any two of the above times.
[0110] In some embodiments, the surfactant includes at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyldimethylbenzylammonium chloride, and dodecyldimethylbenzylammonium chloride.
[0111] In some embodiments, in the second dispersed system, the concentration of the surfactant is 2 mg / mL to 10 mg / mL.
[0112] Optionally, in the second dispersed system, the concentration of the surfactant is 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL or 10 mg / mL, or, in the second dispersed system, the concentration of the surfactant may also be within the range between any two of the above concentrations.
[0113] In some embodiments, the second dispersion medium includes deionized water and a second organic solvent.
[0114] In some embodiments, the second organic solvent includes at least one of ethanol, methanol, acetone, ethylene glycol, isopropanol and nitrogen methyl pyrrolidone.
[0115] In some of the embodiments, in the second dispersion medium, the volume ratio of the second organic solvent to deionized water is 1:(1-1.5).
[0116] Optionally, in the second dispersion medium, the volume ratio of the second organic solvent to deionized water is 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5, or, in the second dispersion medium, the volume ratio of the second organic solvent to deionized water may also be within the range between any two of the above volume ratios.
[0117] In some embodiments, mixing the solid phase graphene raw material, the inorganic corrosion inhibitor and the surfactant in the second dispersion medium to obtain the second dispersion system comprises the following steps:
[0118] Dispersing the solid-phase graphene raw material in the second dispersion medium by ultrasonic treatment for 10 min to 30 min;
[0119] An inorganic corrosion inhibitor and a surfactant are added to the second dispersion medium.
[0120] In some embodiments, the second dispersion medium is also stirred during the heat preservation process.
[0121] S50: centrifuging the second dispersed system at a speed of 9000 rpm to 12000 rpm to obtain a modified graphene precipitate; freeze-drying the modified graphene precipitate at -40°C to -20°C, and crushing and sieving to obtain a modified graphene powder.
[0122] In some embodiments, the second dispersed system is centrifuged at a speed of 9000 rpm to 12000 rpm for 30 min to 60 min.
[0123] In some embodiments, the freeze-drying time is 24 h to 36 h.
[0124] Optionally, the second dispersed system is centrifuged at a rotation speed of 9000 rpm, 10000 rpm, 11000 rpm or 12000 rpm, or the second dispersed system is centrifuged at a rotation speed within a range between any two of the above rotation speeds.
[0125] Optionally, the time for centrifuging the second dispersed system at a speed of 9000 rpm to 12000 rpm is 30 min, 40 min, 50 min or 60 min, or the time for centrifuging the second dispersed system at a speed of 9000 rpm to 12000 rpm can also be within the range between any two of the above times.
[0126] Optionally, the freeze-drying temperature is -40°C, -35°C, -30°C, -25°C or -20°C, or, the freeze-drying temperature may be within a range between any two of the above temperatures.
[0127] Optionally, the freeze-drying time is 24 h, 26 h, 28 h, 30 h, 32 h, 34 h or 36 h, or, the freeze-drying time may also be within the range between any two of the above times.
[0128] Another embodiment of the present application provides a modified graphene prepared by any of the above-mentioned methods for preparing modified graphene, comprising a graphene main body, an organic acid and an inorganic corrosion inhibitor; the inorganic corrosion inhibitor is loaded on the graphene main body through the organic acid.
[0129] The modified graphene of the present application can be used as a filler to fill the gaps in the anti-corrosion coating, play a physical barrier role to resist the penetration of corrosive media, and can also inhibit the occurrence of corrosion through the loaded corrosion inhibitor, achieving the dual effects of physical and chemical protection. At the same time, the modified graphene is evenly dispersed and not easy to agglomerate, and can achieve a relatively stable anti-corrosion filler effect.
[0130] Another embodiment of the present application provides the use of the above-mentioned modified graphene or the modified graphene prepared according to any of the above-mentioned methods for preparing modified graphene as an anti-corrosion filler in an anti-corrosion coating.
[0131] The following are specific embodiments
[0132] Example 1
[0133] Preparation method of modified graphene:
[0134] (1) Disperse 0.6 g of polyvinyl alcohol and 6 g of citric acid in 200 ml of deionized water with magnetic stirring, heat to boiling, and continue magnetic stirring at 90°C for 30 min to fully dissolve the polyvinyl alcohol and citric acid. Take 6 g of graphite powder (300 mesh) and add it to 300 ml of ethanol, and then add the solution prepared in the above steps, and continue to add deionized water and ethanol to make the total solution volume 600 ml and the volume ratio of water to ethanol is 1:1, then shear at a speed of 10000 rpm in an ice water bath for 1 h to obtain a graphene suspension;
[0135] (2) The graphene suspension is centrifuged at 500 rpm for 60 min to remove the large pieces of graphite that are not fully exfoliated, and the supernatant is the graphene dispersion; the graphene dispersion is centrifuged at 10,000 rpm for 30 min to collect the precipitated graphene raw materials;
[0136] (3) The graphene raw material was redispersed in 50 ml of a mixture of water and ethanol (volume ratio 5:5), and low-power ultrasound was applied for 20 min to redisperse the graphene; then 0.15 g of hydrated cerium nitrate and 0.1 g of hexadecyltrimethylammonium bromide were added, and then magnetic stirring was performed at a water bath temperature of 60°C for 3 h;
[0137] (4) The reaction solution in step (3) was centrifuged again at a speed of 10000 rpm for 30 min to obtain cerium salt-modified graphene, and the cerium salt-modified graphene was freeze-dried at -30°C for 24 h, crushed and passed through a 300-mesh sieve to obtain modified graphene powder.
[0138] The modified graphene prepared in Example 1 was ultrasonically cleaned for 10 min using a 150 W ultrasonic cleaner and dispersed in water or ethanol. The modified graphene had excellent dispersibility and no obvious precipitation occurred after standing for 2 weeks.
[0139] In order to study the groups contained in the graphene powder and the surface defect information, the graphene in Example 1 was subjected to Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy (Raman). Figure 2 As shown in a, Figure 2 a is the FTIR spectrum of polyvinyl alcohol, graphite and graphene. The spectral lines of polyvinyl alcohol and graphene are both at 3460 cm -1 There is an obvious -OH stretching vibration absorption peak at the position, which is much stronger than that of graphite. This may be due to the presence of polyvinyl alcohol on the graphene surface, which greatly increases the number of hydroxyl groups. Figure 2 As shown in b, Figure 2 b is the Raman spectrum of graphite and graphene. Both spectral lines are around 1340 cm -1 ~1350cm -1and about 1570cm -1 ~1580cm -1 The typical D peak and G peak appear at the positions of the graphene structure. The ratio of the two peaks, ID / IG, can reflect the defect density in the graphene structure. The calculated ID / IG value of graphene is very low (only 0.08), indicating that high-quality graphene is obtained by exfoliation, and its defects are planar edge defects rather than in-plane defects. Figure 3 As shown, Figure 3 a is the FTIR spectra of modified graphene (Ce-Gr), graphene and graphite powder in Example 1, Figure 3 Figure b is the Raman spectra of the modified graphene (Ce-Gr), graphene and graphite powder in Example 1. Figure 3 As shown in a, the infrared spectrum of Ce-Gr is located at 1382cm -1 A new absorption peak appears at the position, which is caused by the stretching vibration of Ce-O-Ce and is the characteristic structure of CeO2. Figure 3 As shown in (b), compared with graphite and graphene, the ID / IG value of Ce-Gr did not increase, indicating that the modification of cerium nitrate did not increase the surface defects of graphene and retained the structural integrity of the graphene sheet.
[0140] Example 2
[0141] Preparation method of modified graphene:
[0142] (1) Disperse 0.6 g of polyvinyl alcohol and 6 g of phytic acid in 200 ml of deionized water with magnetic stirring, heat to boiling, and continue magnetic stirring at 80°C for 40 min to fully dissolve the polyvinyl alcohol and phytic acid. Take 6 g of graphite powder (500 mesh) and add it to 300 ml of ethanol, and then add the solution prepared in the above steps, and continue to add deionized water and ethanol to make the total solution volume 600 ml and the volume ratio of water to ethanol is 1:1, then shear at a speed of 10000 rpm in an ice water bath for 1 h to obtain a graphene suspension;
[0143] (2) The graphene suspension was centrifuged at 600 rpm for 30 min to remove the large pieces of graphite that were not fully exfoliated, and the supernatant was the graphene dispersion; the graphene dispersion was centrifuged at 11000 rpm for 40 min to collect the precipitated graphene raw materials;
[0144] (3) The graphene raw material was redispersed in 50 ml of a mixture of water and ethanol (volume ratio 5:5), and low-power ultrasound was applied for 30 min to redisperse the graphene; then 0.2 g of cerium chloride and 0.1 g of hexadecyltrimethylammonium bromide were added, and then magnetic stirring was performed at a water bath temperature of 60°C for 3 h;
[0145] (4) The reaction solution in step (3) was centrifuged again at a speed of 10000 rpm for 20 min to obtain cerium salt-modified graphene, and the cerium salt-modified graphene was freeze-dried at -40°C for 24 h, crushed and passed through a 300-mesh sieve to obtain modified graphene powder.
[0146] The modified graphene prepared in Example 2 was ultrasonically cleaned for 10 min in a 150 W ultrasonic cleaner and dispersed in water or ethanol. The modified graphene had excellent dispersibility and no obvious precipitation was observed after standing for 2 weeks.
[0147] Example 3
[0148] Preparation method of modified graphene:
[0149] (1) Disperse 0.8 g of polyvinyl alcohol and 8 g of citric acid in 200 ml of deionized water with magnetic stirring, heat to boiling and continue magnetic stirring at 95°C for 50 min to fully dissolve the polyvinyl alcohol and citric acid. Take 8 g of graphite powder (500 mesh) and add it to 300 ml of ethanol, and then add the solution prepared in the above steps, and continue to add deionized water and ethanol to make the total solution volume 600 ml and the volume ratio of water to ethanol is 1:1, then shear at a speed of 11000 rpm in an ice water bath for 2 h to obtain a graphene suspension;
[0150] (2) The graphene suspension is centrifuged at 500 rpm for 60 min to remove the large pieces of graphite that are not fully exfoliated, and the supernatant is the graphene dispersion; the graphene dispersion is centrifuged at 10,000 rpm for 60 min to collect the precipitated graphene raw materials;
[0151] (3) The graphene raw material was redispersed in 50 ml of a mixture of water and ethanol (volume ratio 5:5), and low-power ultrasound was applied for 40 min to redisperse the graphene; then 0.2 g of cerium chloride and 0.15 g of hexadecyltrimethylammonium bromide were added, and then magnetic stirring was performed at a water bath temperature of 60°C for 2 h;
[0152] (4) The reaction solution in step (3) was centrifuged again at a speed of 11000 rpm for 20 min to obtain cerium salt-modified graphene, and the cerium salt-modified graphene was freeze-dried at -35°C for 36 h, crushed and passed through a 300-mesh sieve to obtain modified graphene powder.
[0153] The modified graphene prepared in Example 3 was ultrasonically cleaned for 10 min in a 150 W ultrasonic cleaner and dispersed in water or ethanol. The modified graphene had excellent dispersibility and no obvious precipitation was observed after standing for 2 weeks.
[0154] Example 4
[0155] Preparation method of modified graphene:
[0156] (1) Disperse 1g of polyvinyl alcohol and 10g of citric acid in 200ml of deionized water with magnetic stirring, heat to boiling and continue magnetic stirring at 95°C for 50min to fully dissolve the polyvinyl alcohol and citric acid. Take 10g of graphite powder (500 mesh) and add it to 300ml of ethanol, and then add the solution prepared in the above steps, and continue to add deionized water and ethanol to make the total solution volume 600ml and the volume ratio of water to ethanol is 1:1, then shear at a speed of 10000rpm in an ice water bath for 1h to obtain a graphene suspension;
[0157] (2) The graphene suspension is centrifuged at 500 rpm for 60 min to remove the large pieces of graphite that are not fully exfoliated, and the supernatant is the graphene dispersion; the graphene dispersion is centrifuged at 11000 rpm for 50 min to collect the precipitated graphene raw materials;
[0158] (3) The graphene raw material was redispersed in 50 ml of a mixture of water and ethanol (volume ratio 5:5), and low-power ultrasound was applied for 30 min to redisperse the graphene; then 0.25 g of cerium chloride and 0.2 g of hexadecyltrimethylammonium bromide were added, and then magnetic stirring was performed at a water bath temperature of 60°C for 2 h;
[0159] (4) The reaction solution in step (3) was centrifuged again at a speed of 10000 rpm for 30 min to obtain cerium salt-modified graphene, and the cerium salt-modified graphene was freeze-dried at -35°C for 24 h, crushed and passed through a 300-mesh sieve to obtain modified graphene powder.
[0160] The modified graphene prepared in Example 4 was ultrasonically cleaned for 10 min in a 150 W ultrasonic cleaner and dispersed in water or ethanol. The modified graphene had excellent dispersibility and no obvious precipitation was observed after standing for 2 weeks.
[0161] Example 5
[0162] Preparation method of modified graphene:
[0163] (1) Disperse 0.8 g of polyvinyl alcohol and 8 g of citric acid in 200 ml of deionized water with magnetic stirring, heat to boiling, and continue magnetic stirring at 85°C for 30 min to fully dissolve the polyvinyl alcohol and citric acid. Take 8 g of graphite powder (300 mesh) and add it to 300 ml of ethanol, and then add the solution prepared in the above steps, and continue to add deionized water and ethanol to make the total solution volume 600 ml and the volume ratio of water to ethanol is 1:1, then shear at a speed of 10000 rpm for 2 h in an ice water bath to obtain a graphene suspension;
[0164] (2) The graphene suspension is centrifuged at 500 rpm for 45 min to remove the large pieces of graphite that are not fully exfoliated, and the supernatant is the graphene dispersion; the graphene dispersion is centrifuged at 10,000 rpm for 45 min to collect the precipitated graphene raw materials;
[0165] (3) The graphene raw material was redispersed in 50 ml of a mixture of water and ethanol (volume ratio 5:5), and low-power ultrasound was applied for 20 min to redisperse the graphene; then 0.15 g of hydrated cerium nitrate and 0.1 g of hexadecyltrimethylammonium bromide were added, and then magnetic stirring was performed at a water bath temperature of 50°C for 3 h;
[0166] (4) The reaction solution in step (3) was centrifuged again at a speed of 10000 rpm for 30 min to obtain cerium salt-modified graphene, and the cerium salt-modified graphene was freeze-dried at -30°C for 24 h, crushed and passed through a 300-mesh sieve to obtain modified graphene powder.
[0167] The modified graphene prepared in Example 5 was ultrasonically cleaned for 10 min in a 150 W ultrasonic cleaner and dispersed in water or ethanol. The modified graphene had excellent dispersibility and no obvious precipitation was observed after standing for 2 weeks.
[0168] Example 6
[0169] Preparation method of modified graphene:
[0170] (1) Disperse 0.1g of polyvinyl alcohol and 1g of citric acid in 200ml of deionized water with magnetic stirring, heat to boiling and continue magnetic stirring at 90°C for 30min to fully dissolve the polyvinyl alcohol and citric acid. Add 15g of graphite powder (300 mesh) to 300ml of ethanol, add the solution prepared in the above steps, and continue to add deionized water and ethanol to make the total solution volume 600ml and the volume ratio of water to ethanol 1:1, then shear at 10000rpm in an ice water bath for 1h to obtain a graphene suspension;
[0171] (2) The graphene suspension is centrifuged at 500 rpm for 60 min to remove the large pieces of graphite that are not fully exfoliated, and the supernatant is the graphene dispersion; the graphene dispersion is centrifuged at 10,000 rpm for 30 min to collect the precipitated graphene raw materials;
[0172] (3) The graphene raw material was redispersed in 50 ml of a mixture of water and ethanol (volume ratio 5:5), and low-power ultrasound was applied for 20 min to redisperse the graphene; then 0.15 g of hydrated cerium nitrate and 0.1 g of hexadecyltrimethylammonium bromide were added, and then magnetic stirring was performed at 70°C in a water bath for 3 h;
[0173] (4) The reaction solution in step (3) was centrifuged again at a speed of 10000 rpm for 30 min to obtain cerium salt-modified graphene, and the cerium salt-modified graphene was freeze-dried at -30°C for 24 h, crushed and passed through a 300-mesh sieve to obtain modified graphene powder.
[0174] The modified graphene prepared in Example 6 was ultrasonically cleaned for 10 min using a 150 W ultrasonic cleaner and dispersed in water or ethanol. The modified graphene had good dispersibility, but precipitation occurred after standing for 5 days.
[0175] Example 7
[0176] Preparation method of modified graphene:
[0177] (1) Disperse 0.2 g of polyvinyl alcohol and 2 g of citric acid in 200 ml of deionized water with magnetic stirring, heat to boiling and continue magnetic stirring at 90°C for 30 min to fully dissolve the polyvinyl alcohol and citric acid. Add 2 g of graphite powder (300 mesh) to 300 ml of ethanol, add the solution prepared in the above steps, and continue to add deionized water and ethanol to make the total solution volume 600 ml and the volume ratio of water to ethanol 1:1, then shear at 10000 rpm in an ice water bath for 1 h to obtain a graphene suspension;
[0178] (2) The graphene suspension is centrifuged at 500 rpm for 60 min to remove the large pieces of graphite that are not fully exfoliated, and the supernatant is the graphene dispersion; the graphene dispersion is centrifuged at 10,000 rpm for 30 min to collect the precipitated graphene raw materials;
[0179] (3) The graphene raw material was redispersed in 50 ml of a mixture of water and ethanol (volume ratio 5:5), and low-power ultrasound was applied for 20 min to redisperse the graphene; then 0.15 g of hydrated cerium nitrate and 0.1 g of hexadecyltrimethylammonium bromide were added, and then magnetic stirring was performed at a water bath temperature of 65°C for 3 h;
[0180] (4) The reaction solution in step (3) was centrifuged again at a speed of 10000 rpm for 30 min to obtain cerium salt-modified graphene, and the cerium salt-modified graphene was freeze-dried at -30°C for 24 h, crushed and passed through a 300-mesh sieve to obtain modified graphene powder.
[0181] The modified graphene prepared in Example 7 was ultrasonically cleaned for 10 min using a 150 W ultrasonic cleaner and dispersed in water or ethanol. The modified graphene had good dispersibility, but precipitation occurred after standing for 7 days.
[0182] Comparative Example 1
[0183] The difference between the preparation method of modified graphene in Comparative Example 1 and Example 1 is that in Comparative Example 1, no dispersant and organic acid are used to modify the graphene.
[0184] Preparation method of modified graphene:
[0185] (1) 6 g of graphite powder (300 mesh) was added to 300 ml of ethanol, and the solution prepared in the above step was added, and deionized water and ethanol were continued to be added to make the total solution volume 600 ml and the volume ratio of water to ethanol was 1:1, and then sheared at a speed of 10000 rpm in an ice water bath for 1 h to obtain a graphene suspension;
[0186] (2) The graphene suspension is centrifuged at 500 rpm for 60 min to remove the large pieces of graphite that are not fully exfoliated, and the supernatant is the graphene dispersion; the graphene dispersion is centrifuged at 10,000 rpm for 30 min to collect the precipitated graphene raw materials;
[0187] (3) The graphene raw material was redispersed in 50 ml of a mixture of water and ethanol (volume ratio 5:5), and low-power ultrasound was applied for 20 min to redisperse the graphene; then 0.15 g of hydrated cerium nitrate and 0.1 g of hexadecyltrimethylammonium bromide were added, and then magnetic stirring was performed at a water bath temperature of 60°C for 3 h;
[0188] (4) The reaction solution in step (3) was centrifuged again at a speed of 10000 rpm for 30 min to obtain cerium salt-modified graphene, and the cerium salt-modified graphene was freeze-dried at -30°C for 24 h, crushed and passed through a 300-mesh sieve to obtain modified graphene powder.
[0189] The modified graphene prepared in Example 1 was ultrasonically cleaned for 10 min in a 150 W ultrasonic cleaner and dispersed in water or ethanol. The modified graphene had poor dispersibility and could not form a uniform dispersion system. Particulate matter existed in the liquid.
[0190] Comparative Example 2
[0191] The difference between the preparation methods of modified graphene in Comparative Example 2 and Example 1 is that in step (3) of Comparative Example 2, no surfactant is added.
[0192] (1) Disperse 0.6 g of polyvinyl alcohol and 6 g of citric acid in 200 ml of deionized water with magnetic stirring, heat to boiling, and continue magnetic stirring at 90°C for 30 min to fully dissolve the polyvinyl alcohol and citric acid. Take 6 g of graphite powder (300 mesh) and add it to 300 ml of ethanol, and then add the solution prepared in the above steps, and continue to add deionized water and ethanol to make the total solution volume 600 ml and the volume ratio of water to ethanol is 1:1, then shear at a speed of 10000 rpm in an ice water bath for 1 h to obtain a graphene suspension;
[0193] (2) The graphene suspension is centrifuged at 500 rpm for 60 min to remove the large pieces of graphite that are not fully exfoliated, and the supernatant is the graphene dispersion; the graphene dispersion is centrifuged at 10,000 rpm for 30 min to collect the precipitated graphene raw materials;
[0194] (3) The graphene raw material was redispersed in 50 ml of a mixture of water and ethanol (volume ratio 5:5), and low-power ultrasound was applied for 20 min to redisperse the graphene; then 0.15 g of hydrated cerium nitrate was added, and then magnetic stirring was applied at 60° C. in a water bath for 3 h;
[0195] (4) The reaction solution in step (3) was centrifuged again at a speed of 10000 rpm for 30 min to obtain cerium salt-modified graphene, and the cerium salt-modified graphene was freeze-dried at -30°C for 24 h, crushed and passed through a 300-mesh sieve to obtain modified graphene powder.
[0196] The modified graphene prepared in Comparative Example 2 was ultrasonically cleaned for 10 min in a 150 W ultrasonic cleaner and dispersed in water or ethanol. The modified graphene had a poor dispersion effect, with obvious granularity in the liquid, and precipitation occurred after standing for half an hour.
[0197] Comparative Example 3
[0198] The difference between Comparative Example 3 and Example 2 is that in step (3) of Comparative Example 3, the mixed liquid is not subjected to heat preservation treatment.
[0199] (1) Disperse 0.6 g of polyvinyl alcohol and 6 g of phytic acid in 200 ml of deionized water with magnetic stirring, heat to boiling, and continue magnetic stirring at 80°C for 40 min to fully dissolve the polyvinyl alcohol and phytic acid. Take 6 g of graphite powder (500 mesh) and add it to 300 ml of ethanol, and then add the solution prepared in the above steps, and continue to add deionized water and ethanol to make the total solution volume 600 ml and the volume ratio of water to ethanol is 1:1, then shear at a speed of 10000 rpm in an ice water bath for 1 h to obtain a graphene suspension;
[0200] (2) The graphene suspension was centrifuged at 600 rpm for 30 min to remove the large pieces of graphite that were not fully exfoliated, and the supernatant was the graphene dispersion; the graphene dispersion was centrifuged at 11000 rpm for 40 min to collect the precipitated graphene raw materials;
[0201] (3) The graphene raw material was redispersed in 50 ml of a mixture of water and ethanol (volume ratio 5:5), and low-power ultrasound was applied for 30 min to redisperse the graphene; then 0.2 g of cerium chloride and 0.1 g of hexadecyltrimethylammonium bromide were added, and then magnetic stirring was performed at room temperature for 2 h;
[0202] (4) The reaction solution in step (3) was centrifuged again at a speed of 10000 rpm for 20 min to obtain cerium salt-modified graphene, and the cerium salt-modified graphene was freeze-dried at -40°C for 24 h, crushed and passed through a 300-mesh sieve to obtain modified graphene powder.
[0203] The modified graphene prepared in Comparative Example 3 was ultrasonically cleaned for 10 min in a 150 W ultrasonic cleaner and dispersed in water or ethanol. The dispersion effect of the modified graphene was poor, the particles in the liquid were obvious, and precipitation occurred after standing for half an hour.
[0204] The stability results of the modified graphene in Examples 1 to 7 and Comparative Examples 1 to 3 are shown in the following table:
[0205]
[0206] In contrast to Example 1 and Comparative Example 1, the graphite powder was directly subjected to shear exfoliation without modification by a dispersant and an organic acid, and the functional groups on the graphene surface were relatively few, resulting in poor dispersibility. It can be seen that in the present application, modified graphene with good dispersibility can be prepared by first modifying with a dispersant and an organic acid, thereby providing suitable reaction sites for the modification process.
[0207] By comparing Example 1 with Comparative Example 2 and Comparative Example 3, it can be seen that the graphene obtained by liquid phase exfoliation needs to be added with a surfactant and heated before it can further react efficiently and selectively with the corrosion inhibitor, so that the corrosion inhibitor and graphene are selectively grafted to prepare modified graphene loaded with corrosion inhibitor and having good dispersibility. When under neutral or room temperature conditions, the activity of the corrosion inhibitor may be reduced, resulting in failure to fully react with graphene, and further resulting in poor dispersibility of the obtained modified graphene.
[0208] By comparing Examples 1 to 7, it can be seen that when the graphite content in Examples 6 and 7 is too high, that is, when the content of the dispersant and the organic acid is too low, the dispersion performance of the modified graphene prepared is slightly worse than that of the modified graphene prepared in Examples 1 to 5, and agglomeration is likely to occur after standing for a long time.
[0209] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0210] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description and drawings may be used to interpret the contents of the claims.
Claims
1. A method for preparing modified graphene, characterized in that: The steps include: Mixing a dispersant, an organic acid and graphite in a first dispersion medium to obtain a first dispersion system, and performing a liquid phase exfoliation treatment on the first dispersion system to obtain a graphene suspension; Removing unpeeled graphite from the graphene suspension to obtain a graphene dispersion; Performing solid-liquid separation on the graphene dispersion to obtain a solid-phase graphene raw material; The solid-phase graphene raw material, the inorganic corrosion inhibitor and the surfactant are mixed in a second dispersion medium to obtain a second dispersion system, and the second dispersion system is subjected to a heat preservation treatment.
2. The method for preparing modified graphene according to claim 1, characterized in that, The dispersant comprises at least one of polyvinyl alcohol, dopamine, sodium polystyrene sulfonate, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone; and / or, The organic acid comprises at least one of citric acid, phytic acid, acetic acid and ascorbic acid; and / or, The inorganic corrosion inhibitor comprises at least one of cerium nitrate, cerium chloride, lanthanum nitrate, lanthanum chloride, lanthanum carbonate, sodium silicate, sodium phosphate and sodium molybdate; and / or, The graphite is 300-1000 mesh graphite.
3. The method for preparing modified graphene according to claim 1, characterized in that, In the first dispersed system, the mass ratio of the organic acid to the graphite is (1-2):10; and / or, In the first dispersed system, the mass ratio of the dispersant to the graphite is (1-2):1; and / or, In the first dispersed system, the concentration of the organic acid is 10 mg / mL to 20 mg / mL; and / or, In the first dispersed system, the concentration of the dispersant is 1 mg / mL to 2 mg / mL; and / or, In the first dispersed system, the concentration of the graphite is 10 mg / mL to 20 mg / mL.
4. The method for preparing modified graphene according to claim 1, characterized in that, In the second dispersed system, the concentration of the solid-phase graphene raw material is 0.5 mg / mL to 2 mg / mL; and / or, In the second dispersed system, the concentration of the inorganic corrosion inhibitor is 3 mg / mL to 6 mg / mL; and / or, The surfactant comprises at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyldimethylbenzylammonium chloride and dodecyldimethylbenzylammonium chloride; and / or, In the second dispersed system, the concentration of the surfactant is 2 mg / mL to 10 mg / mL; and / or, The temperature of the heat preservation treatment is 40°C to 90°C; and / or, The time of the heat preservation treatment is 2h~3h.
5. The method for preparing modified graphene according to claim 1, characterized in that, A dispersant, an organic acid and graphite are mixed in a first dispersion medium to obtain a first dispersion system, and liquid phase exfoliation treatment of the first dispersion system comprises the following steps: Dissolving the dispersant and the organic acid in deionized water to obtain a first solution; Dispersing the graphite in a first organic solvent to obtain a first dispersion; The first solution and the first dispersion are mixed, and the mixed solution is sheared at a rotation speed of 10000 rpm to 15000 rpm.
6. The method for preparing modified graphene according to claim 1, characterized in that: Removing the unpeeled graphite in the graphene suspension comprises the following steps: The graphene suspension is centrifuged at a rotation speed of 500 rpm to 1000 rpm to precipitate the unexfoliated graphite to obtain the graphene dispersion.
7. The method for preparing modified graphene according to claim 1, characterized in that: The solid-liquid separation process of the graphene dispersion comprises the following steps: The graphene dispersion is centrifuged at a speed of 9000 rpm to 12000 rpm to obtain a graphene precipitate.
8. The method for preparing modified graphene according to any one of claims 1 to 7, characterized in that: After the second dispersed system is subjected to heat preservation treatment, the method further comprises the following steps: Centrifuging the second dispersed system at a speed of 9000 rpm to 12000 rpm to obtain a modified graphene precipitate; The modified graphene is precipitated and freeze-dried at -40°C to -20°C, and then crushed and sieved to obtain modified graphene powder.
9. A modified graphene, characterized in that: The modified graphene is prepared by the preparation method of any one of claims 1 to 8, comprising a graphene main body, an organic acid and an inorganic corrosion inhibitor; the inorganic corrosion inhibitor is loaded on the graphene main body through the organic acid.
10. Use of the modified graphene according to claim 9 or the modified graphene prepared by the preparation method of the modified graphene according to any one of claims 1 to 8 as an anti-corrosion filler in an anti-corrosion coating.
Citation Information
Patent Citations
Anticorrosive paint based on phytic acid modified graphene, and preparation method thereof
CN110054969A
Fluorinated graphene / CeO2 nano-composite modified anti-corrosive coating and preparation method thereof
CN112175477A
Cerium salt modified graphene / epoxy powder coating as well as preparation and application thereof
CN117946563A